2019
DOI: 10.1029/2018gl079881
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Variability Controls Denitrification in the Bay of Bengal Oxygen Minimum Zone

Abstract: Nitrate limits productivity in much of the ocean. Nitrate residence time is a few thousand years, and changes in nitrate loss could influence ocean productivity. Major sinks for nitrate are denitrification and anaerobic ammonia oxidation in the oxygen minimum zones (OMZs). The Bay of Bengal OMZ is anomalous because large amounts of nitrate loss do not occur there, while nitrate is removed in the nearby OMZ of the Arabian Sea. Observations of nitrate and oxygen made over 5 years by 20 profiling floats equipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…In the Bay of Bengal, strong interannual variations in the intensity of the eddy activity have been reported (Chen et al, 2012). These are expected to cause strong variations in the subsurface ventilation that may eventually lead to deoxygenation and onset of denitrification at the core of the OMZ (Johnson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Bay of Bengal, strong interannual variations in the intensity of the eddy activity have been reported (Chen et al, 2012). These are expected to cause strong variations in the subsurface ventilation that may eventually lead to deoxygenation and onset of denitrification at the core of the OMZ (Johnson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, even a small decline in oxygen concentrations has significant biogeochemical implications. For example, Bristow et al (2017) showed that the low oxygen concentration enables anaerobic microbial processes within the OMZ of the Bay of Bengal even though a constant physical oxygen supply (Johnson et al, 2019) maintained a oxygen levels of 0.01 -0.2 µM. This suffices to support nitrite oxidization and the resulting lack of nitrite strongly reduced, but probably did not prevent, denitrification.…”
Section: Recent Trends In the Bay Of Bengal And The Arabian Seamentioning
confidence: 99%
“…Given the ability of a float array to make observations on seasonal to interannual timescales at basin to global scales, significant effort has been devoted to integrating biogeochemical sensors onto profiling floats, including oxygen [78,79], nitrate [80], and bio-optical measurements for chlorophyll a fluorescence [81] and particle backscatter [82]. These biogeochemical profiling floats have been used to study production dynamics [83][84][85][86][87], nutrient delivery to oligotrophic waters [88], oxygen minimum zone dynamics [89], regional air-sea fluxes [90][91][92], and elemental ratios [93]. A pCO 2 sensor has been integrated onto a profiling float [94], but has not left the prototyping phase due to issues such as long response time, need for frequent recalibration, and high power requirements.…”
Section: Global Ocean Observations From Profiling Floatsmentioning
confidence: 99%
“…This points towards a production of a considerable part of organic matter produced by diatoms in symbiotic association with or in close proximity to diazotrophs (Subramaniam et al, 2008). Only few studies report the presence of diazotrophs including Trichodesmium in the BoB (Wu et al, 2019;Shetye et al, 2013;Sahu et al, 2017;Jyothibabu et al, 2006;Mulholland and Capone, 2009), with only one of them using a functional gene approach.…”
Section: Introductionmentioning
confidence: 99%